Palaeogeographical reconstruction and management challenges of an archaeological site listed by UNESCO: the case of the Letoon shrine in the Xanthos Plain (Turkey) - Fouache, Eric; Ecochard, Emilie; Kuzucuoğlu, Catherine; Carcaud, Nathalie; Ekmekçi, Mehmet; Ulusoy, Inan; Çiner, Attila; des Courtils, Jacques (Quaestiones Geographicae, 2012)
During the Hellenistic period, Xanthos and Letoon were respectively a large city and an important shrine in Lycia. Questions still remain about the geography of the Eşen Çayı delta during the first millennium BC: what were the features of the landscape surrounding the Letoon shrine? Where did the riverbed lie? Our analysis is based on a reconstruction of the geomorphological dynamics at work during the Holocene. These are then compared with historical, archaeological and literary sources. Sedimentary sampling shows that a marine bay was gradually closed during the formation of a coastline spit, which led to the development of a lagoon system. Lagoons and marshes remained predominant characteristics of the plain over a long period. A branch or a former channel of the Eşen Çayı was discovered close to the Letoon shrine. In recent decades, authorities, as well as UNESCO, are now making an effort to manage palaeoenvironmental reconstructions in their promotion of the tourist potential of archaeological sites. We propose a management project for the Letoon site.